2012
DOI: 10.1530/rep-12-0217
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial inflammation and effect on implantation improvement and pregnancy outcome

Abstract: Implantation failure, which is presently the major barrier in human fertility, is attributed, in many cases, to the failure of the uterus to acquire receptivity. The transition into a receptive uterus includes cellular changes in the endometrium and the modulated expression of different cytokines, growth factors, transcription factors, and prostaglandins. These molecules partake in the generation of an inflammatory response followed by the recruitment of immune cells. These cells have shown to be involved in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
144
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(157 citation statements)
references
References 83 publications
3
144
1
9
Order By: Relevance
“…In fact, a KEGG pathway analysis indicated that a number of genes related to natural killer cell cytotoxicity are up‐regulated in thin endometria, suggesting the presence of a cytotoxic condition. Aberrant immunological factors play roles in recurrent miscarriage and implantation failure 6, 26, 27. Interestingly, 56.6% of the patients who experienced embryo implantation failures showed local immune overactivation in the endometrium at the mid‐luteal phase 6.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a KEGG pathway analysis indicated that a number of genes related to natural killer cell cytotoxicity are up‐regulated in thin endometria, suggesting the presence of a cytotoxic condition. Aberrant immunological factors play roles in recurrent miscarriage and implantation failure 6, 26, 27. Interestingly, 56.6% of the patients who experienced embryo implantation failures showed local immune overactivation in the endometrium at the mid‐luteal phase 6.…”
Section: Discussionmentioning
confidence: 99%
“…These cells have potential inflammatory and antigen-presenting cell functions that could be detrimental to the fetus if the cells were over-activated in response to infection. 7,8,13,14,17,22 CD14 is part of a cognate receptor complex, which includes TLR4 and myeloid differentiation factor 2 and is involved in Mw detection of Gram-negative bacteria via binding to the outer-wall component LPS. 56 IFN-c-primed Mws produced higher levels of pro-inflammatory cytokines and chemokines after stimulation with LPS via the upregulation of CD14, TLR4 and myeloid differentiation factor 2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Whereas gestation has long been recognized as an antiinflammatory Th2 condition, recent studies demonstrated that the process of blastocyst implantation requires a pro-inflammatory Th1 environment. 13,14 The transitory maintenance of this Th1 environment appears to be essential for the growth and survival of trophoblast cells, which in turn produce a balance of pro-and anti-inflammatory cytokines that are linked to the control of leukocyte recruitment, to the regulation of inflammatory activity, and to the promotion of Th2 immune responses. 14 Among the numerous cytokines produced at the implantation site, IFN-c and TNF-a are potent inducers of the pro-inflammatory type-1 phenotype in tissue Mws; 15 in the context of the developing embryo, these cytokines have both beneficial and harmful attributes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Th1 (pro-inflammatory) molecules such as tumor necrosis factor alpha (TNFA) and IFNgamma (IFNG) are also necessary for uterine receptivity, implantation, and placental development in some species (Ashkar & Croy 2001, Hess et al 2007, Paulesu et al 2010, Warning et al 2011, Granot et al 2012. Moreover, type I IFNs play an indisputable role during early pregnancy in ruminants, as the conceptus signals its presence to the mother by producing high levels of interferon tau (IFNT).…”
Section: Introductionmentioning
confidence: 99%